2006
DOI: 10.1002/bit.21180
|View full text |Cite
|
Sign up to set email alerts
|

Effect of solvent concentration on the extraction kinetics and diffusivity of Cyclosporin A in the fungus Tolypocladium inflatum

Abstract: ABSTRACT:The kinetics of solid-liquid extraction and extraction yields of the immunosuppressant drug Cyclosporin A (CyA) from the mycelia of Tolypocladium inflatum were examined in this study. A 2 L stirred, baffled vessel was used to extract CyA from wet mycelia mass. Three different organic solvents were used, namely, methanol, acetone, and isopropanol at different concentrations in aqueous mixtures at room temperature. It was found that the best solvent was acetone at 50% v/v concentration achieving 100% ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…To evaluate the mass transfer rate of extracted solute from the solid matrix surface to the bulk liquid phase, a kinetic approach based on the Fick's law can be used (Ly et al . 2007):…”
Section: Mathematical Modelsmentioning
confidence: 99%
“…To evaluate the mass transfer rate of extracted solute from the solid matrix surface to the bulk liquid phase, a kinetic approach based on the Fick's law can be used (Ly et al . 2007):…”
Section: Mathematical Modelsmentioning
confidence: 99%
“…It was found that the conventional extraction process showed a first-order reaction release pattern while the combined process followed second-order kinetics possibly because of easy disruption of relatively rigid algal cell membranes [14]. It was observed that during the conventional extraction process the external mass transfer resistance was important since generally the dissolution of lipids by the solvent and the external mass transfer occur in the opposite direction in the extraction processes, including the penetration of outer cell walls by the solvent [15]. It was also interesting that two steps were observed in extracting the lipids during the conventional extraction process: the initial slow stage for the first 1 hr and the later faster stage after 2–5 hrs.…”
Section: Resultsmentioning
confidence: 99%
“…CyA is an intracellular metabolite located in the fungal vacuole (Ly et al 2007). It is produced in liquid medium, and the filtration step in the extraction process allows determining the amount of mycelium (dry weight) for each sample.…”
Section: Cyclosporine a Analysismentioning
confidence: 99%